2018
DOI: 10.1007/s00276-018-2147-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the primary ossification center of the fibular shaft in the human fetus

Abstract: PurposesPrecise morphometric data on the development of ossification centers in human fetuses may be useful in the early detection of skeletal dysplasias associated with delayed ossification center development and mineralization. The present study was performed to quantitatively examine the primary ossification center of the fibular shaft with respect to its linear, planar and volumetric parameters.Materials and methodsUsing methods of CT, digital-image analysis (Osirix 3.9 MD) and statistics (Student’s t-test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Ultrasonography and radiological methods, such as x-rays and computed tomography, are used in order to better assess bone ossification and tooth formation [10][11][12]. Earlier relevant studies in the Polish population were based on anthropometric measurements of bone shafts and primary ossification centers in the skull [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography and radiological methods, such as x-rays and computed tomography, are used in order to better assess bone ossification and tooth formation [10][11][12]. Earlier relevant studies in the Polish population were based on anthropometric measurements of bone shafts and primary ossification centers in the skull [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the development of the lower limb consists mainly of its growth [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The actual process of "intracartilaginous ossification" is triggered shortly thereafter, around GD14-GD15 in mouse, when the hypertrophic chondrocytes in the center of the cartilage anlage become invaded by blood vessels along with osteoclasts and osteoprogenitors from the surrounding perichondrium [14]. As a result, the cartilage anlage is progressively eroded and replaced by trabecular bone and bone marrow, a region initially termed the POC [21]. The ends of the long bones (with the exception of the metatarsals and phalanges) start to show epiphysis shaping (Figure 3).…”
mentioning
confidence: 99%